Pengaruh Adversity Quotient, Efikasi Diri, dan Need For Achievement Terhadap Intensi Berwirausaha Mahasiswa (Studi Kasus pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang) - Asmi Zuri Nawu; Nur Diana; Dewi Diah Fakhriyyah (Universitas Islam Malang, 2023)
The purpose of this research is to find out how much influence the adversity quotient, self-efficacy, and need for achievement have on student entrepreneurial intentions. The method used in this research is purposive sampling. The independent variables are adversity quotient, self-efficacy, and need for achievement, while the dependent variable is entrepreneurial intention. The number of samples used in this study were 89 respondents with the criteria of active undergraduate students at the Faculty of Economics and Business in 2019 and 2020 who had taken entrepreneurship courses and were not running a private business. The analytical method used is multiple linear regression test, instrument test, normality test, classical assumption test, and hypothesis testing using SPSS software. The results in this study indicate that adversity quotient has a significant positive effect on entrepreneurial intention, self-efficacy has a significant positive effect on entrepreneurial intention, and need for achievement has a significant positive effect on entrepreneurial intention. This research contributes to the theory of planned behavior.Keywords: Adversity quotient, self-efficacy, need for achievement, entrepreneurial intention.